Physical Activity in Polycythemia Vera: Benefits, Risks and Evidence-Based Exercise Recommendations - A Narrative Review - Ściebura, Kacper; Mordal, Natalia; Zienkiewicz, Damian; Makulec, Gabriela; Domosud, Karolina; Walendziak, Weronika; Wiśniewska, Wiktoria; Ostaszewska, Magdalena; Majchrzyk, Milena; Malczyk, Anna (Quality in Sport, 2026)
Background. Polycythemia vera (PV) is a type of Philadelphia-negative myeloproliferative neoplasm (MPN) associated with a good prognosis but possible serious complications. Although medications lower hematocrit and reduce thrombosis risk, patients and clinicians underuse non-drug approaches such as physical activity (PA), despite growing evidence for their help while dealing with the disease’s symptoms and complications. Aim: This study aims to identify and evaluate the safest and most effective types of physical activity specifically recommended for patients diagnosed with PV. Methods: A brief review of studies examining physical activity in patients with PV or other MPNs was conducted using PubMed, ScienceDirect, American Society of Hematology publications and Google Scholar. Results: Regular PA of moderate intensity, such as walking, swimming, or cycling, for 150–300 minutes per week is safe in well-controlled PV (hematocrit < 45%). This level of activity reduces the most common PV complication - fatigue - by 30–50%, but also soothes aquagenic pruritus, especially during water-based exercise, helps with concentration problems, and decreases bone or muscle pain. Discussion and conclusions: Tailored physical activity for patients with polycythemia vera shows promising results in reducing common symptoms. However, further research is needed to develop optimal activity recommendations for all patient groups.